Effect of surface functionalization on the properties (rheological, mechanical, and dielectric) and microtopography of PEN/CPEN‐f‐CNTs nanocomposites. Issue 9 (19th June 2015) - Pu, Zejun; Zheng, Penglun; Jia, Kun; Liu, Xiaobo
Abstract : Novel carboxylic poly(arylene ether nitrile)s (CPEN) functionalized carbon nanotubes (CPEN‐ f ‐CNTs) were successfully prepared by a simple and effective solvent–thermal route. The CPEN‐ f ‐CNTs were subsequently used as the novel filler for preparation of high performance poly(arylene ether nitrile)s (PEN) nanocomposites. The SEM characterization of the PEN nanocomposites revealed that the CPEN‐ f ‐CNTs present better dispersion and interfacial compatibility in the PEN matrix, which was confirmed by the linear rheological analysis (Cole–Cole plots) as well. Consequently, the improved thermal stability (increased initial and maximum decomposition temperature) and enhanced mechanical properties (tensile strength and modulus) were obtained from nanocomposites using CPEN‐ f ‐CNTs. More importantly, the PEN/CPEN‐ f ‐CNTs nanocomposites not only show a high dielectric constant but also have low dielectric loss. For example, a dielectric constant of 39.7 and a dielectric loss of 0.076 were observed in the PEN composite with 5 wt% CPEN‐ f ‐CNTs loading at 100 Hz. Therefore, the flexible PEN/CPEN‐ f ‐CNTs nanocomposites with outstanding mechanical, thermal and dielectric properties will find wide application in the high energy density capacitors. POLYM. COMPOS., 37:2622–2631, 2016. © 2015 Society of Plastics Engineers